Draft environmental impact statement for the wilderness recommendation, Cape Krusenstern National Monument, Alaska. - United States. National Park Service. Alaska Regional Office. (Anchorage, Alaska : Alaska Regional Office, National Park Service, 1988)
"NPS D-8"--P. [3] of cover. Includes index. "April 1988"--P. [3] of cover. Bibliography: p. 80-84. Mode of access: Internet.